2014
DOI: 10.1080/07448481.2014.936440
|View full text |Cite
|
Sign up to set email alerts
|

Current Versus Ideal Skin Tones and Tanning Behaviors in Caucasian College Women

Abstract: The data suggest that the young Caucasian women in this sample tend to be dissatisfied with their current skin tone to an extent that leads the majority of them to engage in risky, potentially cancer-causing behavior by either salon tanning or considering tanning in the future as time and finances become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…These high rates of tanning before the age of 30 can lead to eight times higher incidence rate of melanoma. Hemrich et al (2014) observed knowledge of the harmful effects of tanning did not deter young women from tanning. Interventions for those that regularly tan should focus on building confidence in one's current appearance rather than attempting to scare out of tanning.…”
Section: Using Sunscreenmentioning
confidence: 89%
See 4 more Smart Citations
“…These high rates of tanning before the age of 30 can lead to eight times higher incidence rate of melanoma. Hemrich et al (2014) observed knowledge of the harmful effects of tanning did not deter young women from tanning. Interventions for those that regularly tan should focus on building confidence in one's current appearance rather than attempting to scare out of tanning.…”
Section: Using Sunscreenmentioning
confidence: 89%
“…There is a correlation between use of tanning beds and incidence of malignant melanoma. Hemrich et al (2014) found that majority of salon tanners were aware of their increased risk for skin cancer, yet they continued this behavior. Many people who had family members diagnosed with a deadly form of skin cancer continued to tan.…”
Section: Using Sunscreenmentioning
confidence: 98%
See 3 more Smart Citations